Sikap Mahasiswa Muslim terhadap Perkembangan Marketplace - Rifki Candra Nugraha; Nida Fitria (ITB AAS INDONESIA Surakarta, 2021)
The purpose of writing this article is to describe the attitudes of Muslim students towards Marketplace developments. The background of this research is that the development of technology is very rapid, causing many fields to be affected by its development. Which one of them is technology in the field of information and communication technology. Internet is born which makes every business easier. One thing that is affected is in the economic sector, especially in the buying and selling process. The presence of the internet has created a place for online transactions called the Marketplace. Currently the Marketplace is very popular with people. Then what is the attitude of Indonesian Muslim students in facing all of this, what is the impact on Muslim students. In this study we used the literature study method, spread out questionnaires and interviews. The results of this research are expected to be taken into consideration in determining attitudes towards Marketplace developments. For future researchers, it is hoped that they can research with a wider time and reach so that the results obtained are more representative.